А rare case of Тakoтsubo cardiomyopathy complicated with high-grade AV block and ventricular tachycardia - M. Peneva; H. Baychev; I. Baltov; L. Abujamus; Ts. Doychinova; H. Nikolov; V. Baycheva; H. Mateev; E. Trendafilova (Българска кардиология, 2023)
Takotsubo cardiomyopathy or broken heart syndrome is a stress-induced cardiomyopathy with clinical, laboratory and ECG resemblance to acute coronary syndrome. Major differences stem from transient segmental wall motion abnormalities beyond the territory of a single coronary artery and the lack of obstructive coronary disease during angiography. Overall the condition is considered as a benign one with a favourable outcome, however there are reports of complicated clinical course by cardiogenic shock, apical thrombus, death and arrhythmias. The latter are reported to occur in 13% of the cases with ventricular arrhythmias (ventricular tachycardia, ventricular ﬁ brillation, torsades de pointes) as a leading ﬁ nding and in minor percentage – high-grade AV block. Despite advances in our knowledge and experience there are still no strict guidelines for the management of conduction disorders. We present the case of a 78-year old lady with an apical variant of Takotsubo, complicated by syncope, complete AV block, new left bundle branch block, paroxysmal atrial ﬁ brillation, ventricular tachycardia and implantation of a permanent pacemaker. During the hospitalization she developed acute cardiac failure with echocardiographic evidence of left ventricular systolic dysfunction and an apical thrombus. The presented case demonstrates the complexity of the condition and the necessity of strict follow-up and timely therapy.